2018
DOI: 10.1111/ceo.13374
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of changes in anterior segment morphology after argon laser peripheral iridoplasty: findings from the EARL study group

Abstract: ALPI results in changes to the angle morphology and lowered IOP in eyes with residual angle closure. Our findings suggest a possible role for ALPI in eyes with residual angle closure following peripheral iridotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(82 reference statements)
2
3
0
Order By: Relevance
“…Tun TA et al also reported that angle opening distance area (AODA) and trabecular-iris space volume (TISV) were significantly increased after LPI when compared with their baseline by CASIA 2 [ 28 ].The decrease in both ITC index and ITC area verified the effectiveness of LPI treatment as well [ 29 ]. The absence of significant change in ACD (pre-LPI 2.03 ± 0.27 mm vs. post-LPI 2.04 ± 0.28 mm) in our study is consistent with previous studies using AS-OCT (pre-LPI 2.03 ± 0.04 mm vs. post-LPI 2.03 ± 0.05 mm) and UBM (pre-LPI 2.41 ± 0.28 mm vs. post-LPI 2.42 ± 0.30 mm) [ 30 , 31 ]. Thus, our study, as well as previous studies, demonstrated that LPI led to a significant anterior chamber angle opening in a reliable and quantifiable manner, while the central ACD did not change after LPI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tun TA et al also reported that angle opening distance area (AODA) and trabecular-iris space volume (TISV) were significantly increased after LPI when compared with their baseline by CASIA 2 [ 28 ].The decrease in both ITC index and ITC area verified the effectiveness of LPI treatment as well [ 29 ]. The absence of significant change in ACD (pre-LPI 2.03 ± 0.27 mm vs. post-LPI 2.04 ± 0.28 mm) in our study is consistent with previous studies using AS-OCT (pre-LPI 2.03 ± 0.04 mm vs. post-LPI 2.03 ± 0.05 mm) and UBM (pre-LPI 2.41 ± 0.28 mm vs. post-LPI 2.42 ± 0.30 mm) [ 30 , 31 ]. Thus, our study, as well as previous studies, demonstrated that LPI led to a significant anterior chamber angle opening in a reliable and quantifiable manner, while the central ACD did not change after LPI.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed neither change in ACD nor LV after LPI, which suggested that treatment with LPI, did not alter the lens position. Similarly, previous studies carried out by AS-OCT and UBM demonstrated that there was no change in these two parameters [ 31 , 42 ].…”
Section: Discussionsupporting
confidence: 67%
“…To date, there have been no randomised controlled trials evaluating the use of iridoplasty in chronic angle-closure caused by PIS. We included seven retrospective case series4 9–15 and one prospective observational case–control study16 published between 2004 and 2017. The study characteristics are described in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The eight studies were conducted on patients with chronic angle-closure persistent after laser peripheral iridotomy. Three studies included both PIS and lens-induced angle closure11 13 16 and five evaluated PIS only 4 10 12–15 17. One study provided a 1-month follow-up,15 five studies a 12-month follow-up,11–13 16 two studies had a long-term follow-up of more than 6 years4 17 and the longest one provided 92.4 months of mean follow-up 10…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation